Characteristics and risk factors of children with sleep-disordered breathing in Wuxi, China - Yun Guo; Zhenzhen Pan; Fei Gao; Qian Wang; Shanshan Pan; Shiyao Xu; Yu Hui; Ling Li; Jun Qian (BMC, 2020)
Abstract Background Sleep-disordered breathing (SDB) is a common syndrome in children, related to their immune responses, cardiovascular function, and neurocognitive function. This study aimed to determine the prevalence of SDB among children in Wuxi, China, and to evaluate the protective and risk factors of SDB in children. Methods A cross-sectional study was conducted on children attending different schools across Wuxi, China, aged 3-14 years old. Of a total of 5630 questionnaires distributed to the parents of the children, 3997 (71.0%) were deemed to be valid. The data on the general sociodemographic factors, children's allergy and sleep characteristics, and the parents' sleep characteristics were also collected. The Paediatric Sleep Questionnaire (PSQ) score was used to identify children at high risk of SDB. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated by logistic regression. Results The prevalence of SDB in this cohort was 13.4% (N = 534). SDB prevalence significantly differed in children with asthma (28.2% vs. 12.8%, P < 0.001), eczema (19.0% vs. 10.0%, P < 0.001), urticaria (16.4% vs. 12.9%, P < 0.01) and rhinitis (21.4% vs. 10.7%, P < 0.001). No significant differences were found in SDB prevalence with respect to pillow material or quilt material. On multivariate logistic regression analysis, asthma (OR 1.986 (95% CI 1.312-3.007), P < 0.01), eczema (OR 1.675 (95% CI 1.377-2.037), P < 0.001), rhinitis (OR 1.998 (95% CI 1.635-2.441), suffered from familial sleep sickness (OR 2.416 (95% CI 1.975-2.955), P < 0.001) and whose mothers slept for a shorter duration (6 h-8 h: OR 1.370 (95% CI 1.089-1.724), P < 0.01; <6 h: OR 3.385(95% CI 2.098-5.461), P < 0.001) increased the odds of having SDB. The incidence of SDB significantly decreased with children's age (6-11 years old: 0R 0.768 (95% CI 0.597-0.989), P < 0.05; 12-14 years old: OR 0.691 (95% CI 0.530-0.901), P < 0.01). Conclusion The results of this study demonstrated that atopic diseases (asthma, eczema, and rhinitis) and family sleep habits were risk factors for SDB in children in Wuxi, China.